A detailed observational study of maternal and neonatal variables affecting the thyroid-stimulating hormone levels in neonates - N. R. Verma; G. Naik; S. Patel; P. Padhi; T. Naik; R. Nanda (Egyptian Pediatric Association Gazette, 2021)
Abstract Background Thyroid hormones are essential for fetal growth and the central nervous system development. Thyroid-stimulating hormone (TSH) is the key regulatory hormone. Their levels are quite dynamic in the perinatal period and are influenced by multiple factors. These factors should be taken into consideration during newborn screening. This study aimed to observe the impact of maternal and neonatal factors on neonatal TSH status. Results Neonatal TSH (nTSH) depicted a positive correlation with parity (p = 0.066) while negative correlation recorded with maternal blood haemoglobin (p = 0.007) among maternal factors. New-born length (p = 0.027) and birth weight (p < 0.001) exhibited a negative correlation with nTSH among neonatal factors. Conclusions This study concludes that among all the maternal and neonatal factors, birth weight shows the most influence on nTSH. However, the effect may be compounded by other factors. As these risk elements rarely occur singly, it is often difficult to find the exposure which confer the risk on children. These factors should be considered while interpreting the result of the screening program.